Uma análise da produção didática da matemática a distância: o caso da UFPB. - Farias, Severina Andréa Dantas de (2009)
This paper presents an analysis of printed educational materials produced by the Universidade Federal da Paraíba - UFPB for the Degree in Mathematics at a Distance. We interviewed five teachers who produced the first printed educational materials, along with the course coordinator. Based on study of the leading theorists in this area as Aretio (2006), Peters (2004), Filatro (2008), Moore (2008), Litto (2009), among others, the Benchmarks for the Ministry of Education (2007) and the Pedagogical Political Project (2006) of this course, we seek to evaluate the suitability of printed educational materials to the reality of distance education, according to standards recognized by the scientific community. The methodology adopted was a qualitative study using a descriptive and documentary in a simple case study, and adopted the strategy of analysis to the standard. The research was conducted at the UFPB and the instrument of data collection was a directed interview, consisting of ten questions. Questions about the construction and preparation of teaching materials printed from the degree produced by his team are not easy to be answered and to rethink this issue this research proposes to reflect on: Teachers authors had already developed some kind of educational material that was used in the classroom? What are the guidelines that these professionals received before starting the development process? What are the difficulties that these professionals had to construct these materials? The teachers know the student profile before starting the preparation of text books? What are the criteria for the choice of content? What are the criteria to choose the language of the text? There was some change in the first volume of the course? How would an ideal teaching material in the view of teachers author After the analysis of the phases of the professionals interviewed based on the theory adopted and the documents we can say that the development and production of teaching first printed volume was not satisfactory, but they are mostly at EAD, as the espoused theory.